2015
DOI: 10.9778/cmajo.20140055
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and newborn outcomes after a prior cesarean birth by planned mode of delivery and history of prior vaginal birth in British Columbia: a retrospective cohort study

Abstract: After 1 or 2 previous cesarean births, risks for adverse outcomes between planned vaginal and cesarean birth are reduced among women with a prior vaginal birth. Our data offer women and their health care providers the opportunity to consider risk profiles separately for women who have and have not had a prior vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…We also found evidence that the mother’s risk of having either a postnatal hospital stay greater than 5 days or an overnight readmission to hospital within 42 days of birth was significantly reduced for women who had a planned VBAC compared to ERCS only if they had any prior vaginal births. This apparent protective effect of prior vaginal delivery is consistent with several previous studies [39,46,47] and might be explained by women with a prior vaginal delivery having less complicated and possibly quicker labors that are more likely to result in a successful VBAC compared to women without a prior vaginal birth [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found evidence that the mother’s risk of having either a postnatal hospital stay greater than 5 days or an overnight readmission to hospital within 42 days of birth was significantly reduced for women who had a planned VBAC compared to ERCS only if they had any prior vaginal births. This apparent protective effect of prior vaginal delivery is consistent with several previous studies [39,46,47] and might be explained by women with a prior vaginal delivery having less complicated and possibly quicker labors that are more likely to result in a successful VBAC compared to women without a prior vaginal birth [16].…”
Section: Discussionsupporting
confidence: 90%
“…The AHRQ review [16] also found evidence that planned VBAC is associated with an increased risk of blood transfusion, but only when the meta-analysis was confined to the four identified studies of women delivered at term rather than any gestational age (pooled estimates: 0.7% for planned VBAC versus 0.5% for ERCS, RR 1.30, 95% CI 1.15–1.47). Since the AHRQ review, although a number of studies have found no significant difference in the risk of blood transfusion between women who had planned VBAC and those that had an ERCS [36,40,42,43], a few of the larger studies have reported an elevated risk of this outcome for planned VBAC [39,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight were population-based studies ( 34 , 36 , 38 , 41 43 , 45 , 50 , 51 , 53 56 , 58 60 , 63 65 , 67 , 69 – 71 , 73 , 75 78 ), while 13 recruited subjects from a single ( 32 , 37 , 39 , 44 , 46 48 , 57 , 61 , 62 , 68 , 72 , 74 ) and six from multiple centers ( 33 , 35 , 40 , 49 , 52 , 66 ). Eighteen of the studies were conducted in mainland Europe ( 34 , 37 , 39 , 41 , 43 , 46 , 48 , 49 , 51 , 56 58 , 60 , 62 , 63 , 66 68 ), 10 in the United States ( 35 , 40 , 42 , 45 , 52 , 55 , 59 , 70 , 71 , 77 ), six in the United Kingdom ( 53 , 54 , 65 , 75 , 76 <...…”
Section: Resultsmentioning
confidence: 99%
“…Uterine rupture was variably defined amongst these studies and the reported absolute risk of rupture varied from 0.00 to 4.76% for planned VBAC and 0.00–2.92% for ERCS. Sixteen of the studies ( 34 , 36 , 40 , 48 , 50 , 51 , 55 , 56 , 58 , 64 , 65 , 70 , 72 , 73 , 77 , 78 ) (seven restricted to women with one prior cesarean) reported an increased risk of uterine rupture for planned VBAC compared to ERCS (relative effect ranging from 1.39 to 243.98), with the highest risks generally apparent when labor was induced and/or augmented. However, one of the studies reported that the risk was only significantly elevated amongst women without a prior vaginal birth ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation